Development of Cold In-Place Recycling with Bitumen Emulsion and Biomass Bottom Ash - Jorge Suárez-Macías; Juan María Terrones-Saeta; Francisco Javier Iglesias-Godino; Francisco Antonio Corpas-Iglesias (Crystals, 2021)
Power generation from biomass is one of the most promising energy sources available today. However, this industry has a series of wastes derived from its activity, mainly biomass fly ash and biomass bottom ash. Biomass bottom ash is a waste that has no current use and, in most cases, is deposited in landfills. In turn, road construction is one of the activities that produces the most pollution, as it requires huge amounts of raw materials. Therefore, this research proposes the use of biomass bottom ashes, in an unaltered form, for the formation of cold in-place recycling with bitumen emulsion. This type of mixture, which is highly sustainable owing to the use of a high percentage of waste, was made with reclaimed asphalt pavement, biomass bottom ash, water, and bitumen emulsion. To this end, the grading curve of the materials was analyzed, different bituminous mixtures were made with varying percentages of emulsion and water, and the mechanical properties of the mixtures were analyzed. At the same time, the same type of mix was made with reclaimed asphalt pavement and commercial limestone aggregate, in order to compare the results. The tests showed a better mechanical behavior of the bituminous mixes made with biomass bottom ash, maintaining physical properties similar to those of conventional mixes. In short, it was confirmed that the production of this type of mix with biomass bottom ash was feasible, creating sustainable materials that reuse currently unused waste and avoid landfill disposal.